Construction in an Open Economy: Autoregressive Distributed Lag Modeling Approach and Causality AnalysisCase of North Cyprus - Yorucu, Vedat (Asce-Amer Soc Civil Engineers, 2013)
This study investigates the long-run equilibrium of the construction sector in an open macroeconomy in which the growth rate and money supply (M3) are exposed to exogenous shocks from foreign capital transfers (FCT). Specifically, the study examines the econometric relationship between M3, FCT, gross domestic product (GDP), and the construction value added (CVA), empirically determining the direction of causality among these variables for North Cyprus. Results reveal that M3 and real GDP are significant determinants of a long-run equilibrium relationship with CVA and FCT, reflecting openness of the capital market in North Cyprus. A positive significant relationship is found between M3 and real GDP in the long run. The results also confirm that CVA is indirectly affected by expansion in M3 and the overall GDP growth during 1977-2008. Most empirical studies and modeling of construction engineering and management are micro level. This study breaks new ground as it attempts to analyze the construction industry within a macro and open economy framework. The findings reported here will benefit especially professionals working on international joint ventures (IJV), interested in securing current strategic positions of IJVs within the competitive environment and formulating strategies to be placed in better performing clusters.
Keywords: Economic factors; Construction industry; Europe; Case studies; Open economy; Economic growth; Autoregressive distributed lag modeling; Bounds test; Causality; International joint venture performances; North Cyprus; Quantitative methods